PENENTUAN TATA LETAK RUANG MENGGUNAKAN WEIGHTED-DISTANCE METHOD DI CV. SUMBER TECHNIK - Lie Liana (Jurnal Ilmiah Dinamika Teknik, 2017)
This study aims to re-layout of six rooms, the delivery room, boardroom, reception room, financial room, administrative space, and space for warehouses that already exist in the CV. Sumber Technik. The layout is done to get the layout of a new, more effective and efficient. His record is a delivery space remains in place, while other spaces that may migrate. This research is applied research. Locations in CV. Sumber Technik engaged in the distribution of building materials. There are six, namely: the delivery room, boardroom, reception room, financial room, administration rooms, and warehouses. Based on the existing layout that will be drawn up the new layout by using the weighted-distance method. There are three stages to go through gathering information, developing a block plan, and then designing the detailed layout. At the stage of gathering information would be obtained space required, the availability of space and the proximity matrix. At the stage of developing a block plan will get some of the proposed block plan. At the stage of designing the layout of the details, which will be achieved proposed block plan are eligible for admission to the criteria of load-distance smaller than the distance from the current load block plan. This shows there is efficiency. To get a load distance calculation is performed using rectilinear distance. Based on the results that the proposed block plan 1 and plan 2 blocks proposed is unacceptable for load distance value is smaller than the distance from the current load block plan. Several other proposed block plan can be made and then calculated load distance. If they meet the criteria then the block plan proposed is acceptable. Keywords : the weighted distance method, block plan, load distance, rectilinear distance.